2009
DOI: 10.1063/1.3072602
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic microsphere-based mixers for microdroplets

Abstract: While droplet-based microfluidic systems have several advantages over traditional flow-through devices, achieving adequate mixing between reagents inside droplet-based reactors remains challenging. We describe an active mixing approach based on the magnetic stirring of self-assembled chains of magnetic microspheres within the droplet as these stirrers experience a rotating magnetic field. We measure the mixing of a water-soluble dye in the droplet in terms of a dimensional mixing parameter as the field-rpm, fl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
56
1
2

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(59 citation statements)
references
References 37 publications
0
56
1
2
Order By: Relevance
“…With reference to several authors [6,10,11,18,26,27], the integrity of a chain is determined by its phase lag which is defined as the angle between the long axis of the chain and the externally applied magnetic field. When this phase lag increases above a critical number, the radial component of the dipolar magnetic force (Eq.…”
Section: A Particle Chain Modelmentioning
confidence: 99%
“…With reference to several authors [6,10,11,18,26,27], the integrity of a chain is determined by its phase lag which is defined as the angle between the long axis of the chain and the externally applied magnetic field. When this phase lag increases above a critical number, the radial component of the dipolar magnetic force (Eq.…”
Section: A Particle Chain Modelmentioning
confidence: 99%
“…37 Within microdroplets, the magnetic particles have also been used to enhance mixing. 38 In this work, polystyrene/silica beads $2.65 mm in diameter with embedded iron oxide nanoparticles were used and chain formation of the magnetic microspheres was observed in rotating magnetic fields. A 500 nL droplet with injected dye solution was observed with video microscopy and quantified via pixel intensity variance.…”
Section: Micromixing Using Magnetic Particlesmentioning
confidence: 99%
“…The half-life of mixing is reduced by more than a factor of 4 when the concentration of beads is increased from 0.5 to 1.5 mg mL À1 . 38 The concurrent use of magnetic particles for droplet transport and mixing would be advantageous for integrated lab-on-a-chip systems.…”
Section: Micromixing Using Magnetic Particlesmentioning
confidence: 99%
“…The feasibility of the method of fluid stirring with a rotating magnet and the magnetic chains was further verified experimentally by Franke et al [62] and by Lee et al [63]; superparamagnetic particles were used in the former study, whereas ferromagnetic particles in the latter. Roy et al [64] demonstrated that even within a micron-sized droplet, the rotating magnetic field can be effectively used to stir the fluid for mixing by manipulating magnetic chains in the same manner as done in a large-size batch mixer. There is an optimum Mason number (ratio of the viscous and the magnetic forces) for the best mixing.…”
Section: Stirring By Particlesmentioning
confidence: 99%